Online Activities, Digital Media Literacy, and Networked Individualism of Korean Youth. (November 2015) - Park, Sora; Kim, Eun-mee; Na, Eun-Yeong
Networked individualism enables Internet users to connect and socialize via their loose and transient multiple networks, whereas digital media literacy is a precondition of effective Internet use. In this study, an attempt has been made to find the link between networked individualism, digital media literacy, and young people's perception of their social capital. A nationally representative face-to-face survey was conducted with Korean adolescents in 2013. Networked individualism was higher in adolescents who frequently engaged in online activities and who demonstrated greater digital media literacy. Belonging to multiple, diverse networks and having many connections was positively correlated to adolescents' online social capital. Findings indicate that online activities and skills influence the ways adolescents connect to others and perceive of their social connectedness.